PERAN INDONESIA DALAM MENANGANI PERDAGANGAN NARKOBA DI WILAYAH PERBATASAN MELALUI KERJASAMA NEGARA ANGGOTA ASEAN TAHUN 2017-2020 - Fiyka Ulfa Mawaddah, (2022)
Abstract Drug trafficking is a form of transnational crime. The presence of this phenomenon has forced the state to build cooperation in dealing with drug trafficking, especially in the region. In the Southeast Asian region, there is ASEAN as a form of regional cooperation. Through ASEAN meetings and commitments are formed for their countries to deal with transnational crimes and continue to conduct evaluations at each meeting. Indonesia as one of the countries that have an important position strives to maintain the security of its country and the region by playing an active role as the main actor in handling trade at the border of Singapore and Malaysia as an ASEAN member country. The role as the main actor is implemented through various active roles by building coordination and cooperation with Singapore and Malaysia, as well as making independent efforts from Indonesia in 2017-2020. In this study, the case was reviewed with the concept of transnational crime, regional cooperation, national interest, and role theory. Using descriptive qualitative methods, with interview techniques and document research. Keywords: Drug trafficking, Indonesia's role, Regional Cooperation, ASEAN